2021
DOI: 10.46310/tjim.832864
|View full text |Cite
|
Sign up to set email alerts
|

From activated charcoal to selective plasma exchange: A retrospective analysis of mushroom poisoning cases treated in the intensive care unit

Abstract: BackgroundThis study aims to evaluate the treatment modalities of adult patients presenting with mushroom poisoning treated in the intensive care unit (ICU) with special consideration of extracorporeal liver support systems. Material and MethodsRecords of patients with mushroom poisoning treated in the ICU between January 2007 and December 2014 were analyzed retrospectively. Results Sixteen adult patients were treated in the ICU for mushroom poisoning during the designated study period. Average time from inges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The most common laboratory finding was increased liver enzymes. And two of the patients had liver failure and underwent liver transplantation [ 55 , 56 ]. The results of another study in Iran that conducted by Silakhori et al showed that the mortality rate of 17 patients poisoned with mushrooms was zero, and only one patient had elevated AST levels without evidence of liver failure [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common laboratory finding was increased liver enzymes. And two of the patients had liver failure and underwent liver transplantation [ 55 , 56 ]. The results of another study in Iran that conducted by Silakhori et al showed that the mortality rate of 17 patients poisoned with mushrooms was zero, and only one patient had elevated AST levels without evidence of liver failure [ 8 ].…”
Section: Discussionmentioning
confidence: 99%